On EWMA Procedure for Detection of a Change in Observations via Martingale Approach - Sukparungsee*, Saowanit; Novikov, Alexander (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Using martingale technique, we present analytic approximations and exact lower bounds for the expectation of the first passage times of an Exponentially Weighted Moving Average (EWMA) procedure used for monitoring changes in distributions. Based on these results, a simple numerical procedure for finding optimal parameters of EWMA for small changes in the means of observation processes is established. Keywords: EWMA, Martingale Approach, First Passage Time, AR (1) Process, Average Run Length, Average Delay, Overshoot. Corresponding author: E-mail: Saowanit.Sukparungsee@student.uts.edu.au